Design and Implementation of a One-Seater Solar Car - Aldandan, Ahmad (2024)
This paper explains the detailed design and implementation process of a solar car. The design of the proposed solar car system represents a broader perspective than that of traditional solar or electric cars. It can be regarded as a hybrid vehicle that integrates solar power as a fundamental aspect of its performance, while also offering the option of direct plug-in charging. The proposed solar-powered four-wheeled car uses two motors to increase the efficiency of power consumption, as both motors generate a relatively high torque and power ratio. The design of the car considers aerodynamics. The solar panel placement has a unique geometric shape that reduces air resistance, thus increasing efficiency and stability on the road. To increase the total rated power to 810 W, six panels were installed on top of the car. Each panel is capable of producing 135 W with an efficiency of 23%. In addition, the car features two identical motor controllers paired with adjacent motors, which contributes to a rear-wheel-drive experience. To safeguard the motor controllers, the system includes protective elements such as an in-line fuse, which is directly connected to the battery. The conducted testing of the implemented car validates the successful and adaptable design, offering promising prospects for an efficient commercial prototype of a solar car.